Quality management concept based on Islamic worldview - Firdaus, Firman Shakti; Md Hussain, Muhammad Nasri; Mohd Asaad, Mohd Norhasni; Yusoff, Rushami Zien (International Academic Research Journal, 2015)
This paper focused on analyzing the concept of quality management based on Islamic Worldview (Tasawwur Islam). The discussion centred on three important areas.Firstly, the analysis on the principle of Islamic Worldview.Secondly, discussing the concept of quality according to Islamic perspective.Finally, this paper analyzed critically the concept of quality management based on Islamic Worldview.This discussion is important because of the role of quality management is critical in the current business environment where the issue oh Halal is pertinent. However, based on the literature analysis, there are still few studies that discuss the concept of quality according to Islamic perspective.This study is base on literature review analysis from published literatures, al-Quran and as-Sunnah.The result of discussion in this paper expected to produce a concept of quality based on Islamic perspective.